Pengaruh Kualitas Pelayanan, Harga dan Suasana Café Terhadap Kepuasan Konsumen Pada Café About Something Palangka Raya - Makarueh, Jeni; Rohaetin, Sri; Erang, Dehen (Edunomics Journal, 2022)
This study aims to determine: 1) Does service quality affect consumer satisfaction, 2) Does price affect consumer satisfaction, 3) Does cafe atmosphere affect consumer satisfaction of all consumers at Cafe About Something Palangka Raya. The method used is descriptive and the determination of the sample does not use the solvin formula because the population is infinity. Sources of data in this study were 96 respondents, while the list of questions was made based on 4 variables, namely: Service Quality, Price, Cafe Atmosphere, Consumer Satisfaction. Interview data collection techniques, observation, and documentation. The data analysis technique used is the percentage of the frequency distribution. The results showed that consumer satisfaction About something coffee on the Service Quality variable was very satisfied, namely 38%, satisfied 46%, quite satisfied 13%, 2% less satisfied, 0.1% dissatisfied, the price variable was very satisfied, namely 27%, satisfied 43% , quite satisfied 25%, less satisfied 5%, atmosphere variable very satisfied that is 31%, satisfied 51%, quite satisfied 15%, dissatisfied 3% . And variable customer satisfaction very satisfied that is 33%, satisfied 49%, quite satisfied 16%. The highest level of consumer satisfaction is in the atmosphere dimension 51% in the "Satisfied" column in the statement The layout or layout in About Something is appropriate and neat and the lowest level of customer satisfaction is in the service quality dimension 3% in the dissatisfied column on the statement that the building facilities in About Something Coffee are complete (toilet, fan, table/chair).